Monetary Policy with a Convex Phillips Curve and Asymmetric Loss - Tambakis, Demosthenes (IMF Working Papers; Working Paper, 1998)
Recent theoretical and empirical work has cast doubt on the hypotheses of a linear Phillips curve and a symmetric quadratic loss function underlying traditional thinking on monetary policy. This paper analyzes the Barro-Gordon optimal monetary policy problem under alternative loss functions-including an asymmetric loss function corresponding to the 'opportunistic approach' to disinflation-when the Phillips curve is convex. Numerical simulations are used to compare the implications of the alternative loss functions for equilibrium levels of inflation and unemployment. For parameter estimates relevant to the United States, the symmetric loss function dominates the asymmetric alternative.